A dignidade da pessoa humana como princípio constitucional de proteção da comunidade LGBTQIA+ - Dil, Gabriel (2021)
This dissertation aims to analyze the performance of the Brazilian Supreme Court in recognizing rights of the LGBTQIA+ community in the face of the unconstitutional omission of the Legislative Branch. For the development of this dissertation, in the research phase, the hypothetical-deductive method was used with a qualitative approach. As for the procedural techniques, these were the bibliographic and documentary, using theoretical foundations to explain the circumstances raised. In this way, the present research was developed in the line of research Constitutional Jurisdiction and Democracy. To this end, the first chapter deals with the history of homoaffectivity and also presents sexual minorities as holders of fundamental rights protected by the Constitution of the Republic Federation of Brazil promulgated in 1988. Therefore, there is talk about the absence of a constitutional culture in Brazil as an obstacle to the realization of the dignity of the human person to LGBTQIA+. The second chapter deals with constitutional jurisdiction as a subsidiary route for recognition of the rights of the LGBTQIA+ community, in light of democratic constitutionalism. In that sense, the last chapter lists the dignity of the human person as a constitutional principle of protection of sexual minorities, with an analysis of the decisions handed down by the Supreme Court Federal Law in which rights were recognized and repaired discriminatory regulatory errors that violated the human dignity of LGBTQIA+ people. It is concluded that LGBTQIA+ rights recognized by the Brazilian Judiciary strengthen the Democratic Rule of Law and do not violate the Constitution of the Federative Republic of Brazil promulgated in 1988, since the interpretations drawn up by the Federal Supreme Court were given by the media itself current constitutional provisions, and in the name of the principle of human dignity. For this reason, It should be noted that the judicialization of these issues does not aim to replace the legislative route, but rather to function as an instrument to protect the human dignity of sexual minorities, while these remain invisible to the majority of Brazilian parliamentarians.